2021
DOI: 10.2337/figshare.14054921
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Randomized, Open-Label Comparison of Once-Weekly Insulin Icodec Titration Strategies Versus Once-Daily Insulin Glargine U100

Abstract: <b>OBJECTIVE</b> <p>Insulin icodec (icodec) is a novel once-weekly basal insulin analog. This trial investigated the efficacy and safety of icodec using different once-weekly titration algorithms.</p> <p><b>RESEARCH DESIGN AND METHODS</b></p> <p>This was a phase 2, randomized, open-label, 16-week, treat-to-target study. Insulin-naïve adults (<i>n</i> = 205) with type 2 diabetes and HbA1c 7–10% while treated with oral glucose-lowering medicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 0 publications
0
13
0
1
Order By: Relevance
“…One unit of icodec has a comparable glucose‐lowering effect to one unit of comparator basal insulin; therefore, at randomization, the ‘once‐weekly’ dose of icodec corresponds to seven times the ‘once‐daily’ dose of comparator basal insulin (the once‐daily basal insulin dose is multiplied by seven) 9‐11 . A summary of comparator interventions is provided in Table 1.…”
Section: Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…One unit of icodec has a comparable glucose‐lowering effect to one unit of comparator basal insulin; therefore, at randomization, the ‘once‐weekly’ dose of icodec corresponds to seven times the ‘once‐daily’ dose of comparator basal insulin (the once‐daily basal insulin dose is multiplied by seven) 9‐11 . A summary of comparator interventions is provided in Table 1.…”
Section: Treatmentsmentioning
confidence: 99%
“…Phase 2 trials conducted among insulin‐naive 9,10 and previously insulin‐treated 11 individuals with T2D have shown good tolerability and glucose‐lowering effects of once‐weekly icodec. Among insulin‐naive individuals, treatment with once‐weekly icodec, with or without background glucose‐lowering agents, was associated with a similar efficacy to once‐daily insulin glargine (glargine) U100, as shown by reductions from baseline in HbA1c.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Daher bedarf Insulin Icodec nur einer 1-mal wöchentlichen Gabe. Verglichen mit Insulin glargin U 100 zeigte Insulin Icodec ähnliche Glukose-senkende Effekte, ohne zu vermehrten Hypoglykämien zu führen, sodass auch das Sicherheitsprofil überzeugend wirkt 23 .…”
Section: Einmal Wöchentliche Basalinsulineunclassified
“…Indeed, in a double‐dummy placebo‐controlled trial in insulin‐naïve patients with T2DM, once‐weekly insulin icodec showed similar glucose‐lowering efficacy as daily glargine U‐100, with no increased incidence of clinically significant or severe hypoglycaemia 65 . Recently, trials evaluating a loading dose of icodec 66 and different titration algorithms 67 have supported the finding that weekly administration of this ultra‐long‐acting insulin formulation can provide comparable or even better glycaemic control than glargine U‐100, without increasing hypoglycaemic risk. A second ultra‐long‐acting formulation in development is basal insulin Fc, in which a novel single‐chain variant of insulin has been combined with a human IgG 2 Fc domain to yield a fusion protein that has a peak‐to‐trough ratio suggestive of a prolonged half‐life 63 .…”
Section: Future Of Basal Insulin Therapymentioning
confidence: 99%